Teori Tindakan Komunikasi Jurgen Habermas sebagai Media Pembebasan Perempuan di Era Digital - Fajar Maulidi; Iqbal, Akhmad (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, IAI Al-Qodiri Jember, 2024)
Gender inequality is often considered a crucial issue for women's existence in their lives. Where the position of men is super-ordinate and women are subordinate. Basically, gender stratification is the result of construction from patriarchal civilization. This research aims to reveal what kind of structure is built by patriarchal civilization and offers a way out by using the theory of the German philosopher Jurgen Habermas who upholds the values of justice and emancipation. This research is library research. Therefore, the data collected is representative literature data and is relevant to the research object. The results of this research reveal firstly, the fundamental problem of oppression of women because there is a social structure that controls (patriarchy dominance). Second, the way out for women's liberation in the current digital era is in accordance with Habermas' offer through the theory of communication action and developing androgynous traits.